Utripanje žarnice - Mohorič, Aleš (Obzornik za matematiko in fiziko, 2012)
An incandescent bulb radiates light because electric current heats up its filament to a very high temperature. The luminosity of an incandescent lamp driven by AC oscillates at double frequency of the current and is out of phase with the electric power supplied because of the finite heat capacity of the filament and the limited rate at which it radiates heat.
Keywords: electric current; električni tok; light bulb; luminosity; nihanje svetilnosti; oscilation; svetilnost; thermal radiation; toplotno sevanje; žarnica